LILRA2 selectively modulates LPS-mediated cytokine production and inhibits phagocytosis by monocytes. - Hao K Lu; Ainslie Mitchell; Yasumi Endoh; Taline Hampartzoumian; Owen Huynh; Luis Borges; Carolyn Geczy; Katherine Bryant; Nicodemus Tedla (PLoS ONE, 2012)
The activating immunoglobulin-like receptor, subfamily A, member 2 (LILRA2) is primarily expressed on the surface of cells of the innate immunity including monocytes, macrophages, neutrophils, basophils and eosinophils but not on lymphocytes and NK cells. LILRA2 cross-linking on monocytes induces pro-inflammatory cytokines while inhibiting dendritic cell differentiation and antigen presentation. A similar activating receptor, LILRA4, has been shown to modulate functions of TLR7/9 in dendritic cells. These suggest a selective immune regulatory role for LILRAs during innate immune responses. However, whether LILRA2 has functions distinct from other receptors of the innate immunity including Toll-like receptor (TLR) 4 and FcγRI remains unknown. Moreover, the effects of LILRA2 on TLR4 and FcγRI-mediated monocyte functions are not elucidated. Here, we show activation of monocytes via LILRA2 cross-linking selectively increased GM-CSF production but failed to induce IL-12 and MCP-1 production that were strongly up-regulated by LPS, suggesting functions distinct from TLR4. Interestingly, LILRA2 cross-linking on monocytes induced similar amounts of IL-6, IL-8, G-CSF and MIP-1α but lower levels of TNFα, IL-1β, IL-10 and IFNγ compared to those stimulated with LPS. Furthermore, cross-linking of LILRA2 on monocytes significantly decreased phagocytosis of IgG-coated micro-beads and serum opsonized Escherichia coli but had limited effect on phagocytosis of non-opsonized bacteria. Simultaneous co-stimulation of monocytes through LILRA2 and LPS or sequential activation of monocytes through LILRA2 followed by LPS led lower levels of TNFα, IL-1β and IL-12 production compared to LPS alone, but had additive effect on levels of IL-10 and IFNγ but not on IL-6. Interestingly, LILRA2 cross-linking on monocytes caused significant inhibition of TLR4 mRNA and protein, suggesting LILRA2-mediated suppression of LPS responses might be partly via regulation of this receptor. Taken together, we provide evidence that LILRA2-mediated activation of monocytes is significantly different to LPS and that LILRA2 selectively modulates LPS-mediated monocyte activation and FcγRI-dependent phagocytosis.